Effect of miR-183-5p on Cholestatic Liver Fibrosis by Regulating Fork Head Box Protein O1 Expression - Wang, Yongxin; Chen, Bin; Xiao, Chengcheng; Yu, Jiang; Bu, Xiangyang; Jiang, Fengxing; Ding, Weijie; Ge, Zhong (Frontiers in Physiology, 2021)
Liver fibrosis is a common pathological feature of end-stage liver disease and has no effective treatment. MicroRNAs (miRNAs) have been found to modulate gene expression in liver disease. But the potential role of miRNA in hepatic fibrosis is still unclear. The objective of this research is to study the potential mechanism and biological function of miR-183-5p in liver fibrosis. In this study, we used high-throughput sequencing to find that miR-183-5p is upregulated in human fibrotic liver tissues. In addition, miR-183-5p was upregulated both in rat liver fibrosis tissue induced by bile-duct ligation (BDL) and activated LX-2 cells (human hepatic stellate cell line) according to the result of quantitative real-time PCR (RT-qPCR). Moreover, the inhibition of miR-183-5p alleviated liver fibrosis, decreased the fibrotic biomarker levels in vitro and in vivo, and led toLX-2 cell proliferation inhibition and, apoptosis induction. The result of dual-luciferase assay revealed that miR-183-5p suppressed fork head box protein O1 (FOXO1) expression by binding to its 3′UTR directly. Next, we used lentivirus to overexpress FOXO1 in LX-2 cells, and we found that overexpression of FOXO1 reversed the promotion of miR-183-5p on liver fibrosis, reducing the fibrotic biomarker levels inLX-2 cells, inhibitingLX-2 cell proliferation, and promoting apoptosis. Furthermore, overexpression of FOXO1 prevented the activation of the transforming growth factor (TGF)-β signaling pathway in TGF-β1-induced LX-2 cells according to the result of western blotting. In conclusion, the findings showed thatmiR-183-5p might act as a key regulator of liver fibrosis, and miR-183-5p could promote cholestatic liver fibrosis by inhibiting FOXO1 expression through the TGF-β signaling pathway. Thus, inhibition of miR-183-5pmay be a new way to prevent and improve liver fibrosis.